PENEGAKAN HUKUM TERHADAP PASAL 137 JUNCTO PASAL 303 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KEPOLISIAN RESOR PELALAWAN - AFRIZAL '; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Traffic and road transport is key to the growth of a community. Community isdependent on land transportation and land transportation is closely related totraffic and road transport. With the increase in demand for transport resulting inviolation of traffic on the highway is likely to cause an accident, there is adiscrepancy tertiban road users and traffic congestion is felt increasing. Trafficviolation is a situation where a discrepancy between the rules andimplementation. The purpose of this study to determine enforcement of Article 137and Article 303 of Law Number 22 Year 2009 regarding Traffic and RoadTransportation, To know the obstacles encountered in enforcement of Article 137and Article 303 of Law No. 22 of 2009 on Road Traffic and Road Transport andTo know the efforts in overcoming obstacles to the enforcement of Article 137 andArticle 303 based on Law Number 22 Year 2009 regarding Traffic and RoadTransportation. Results of this research is the enforcement of the law againstArticle 137 in conjunction with Article 303 of Law Number 22 Year 2009regarding Traffic and Road Transportation in the jurisdiction of PolicePalalawan Palalawan implemented by the Police and the Civil ServantInvestigators Pelalawan District Department of Transportation is to carry out lawenforcement by way of giving out warnings or messages on roadside Area pairsand perform routine outreach to the community and employers who use pickupsas mass transit.Key words: Law enforcement - pickups